Black Women and/in the Shadow of Romanticism. Issue 3 (4th May 2019) - Diaby, Bakary
ABSTRACT: This essay argues that the study of Blackness in Romanticism centers on the spectacularity of violence to Black men and on work by white abolitionists. The result is the marginalization of Black women in Romantic studies proper. After discussing some of the major causes of this phenomenon, the essay offers three principles to help Romantic scholarship move Black women from Romanticism's margins to its center: do the work; think about the everydayness of race; and "don't forget the women." It ends with an appeal to recover the work of Eva B. Dykes, the first Black woman to qualify for a doctorate degree in the United States and the author of The Negro in English Romantic Thought (1942).